Customer satisfaction in Luxury Hotels in Hong Kong: Investigate the role of service quality - Wong, Anthony Tik Tsuen (International Journal of Scientific Research and Management (IJSRM), 2021)
Hong Kong is a tourist hub with a famous name tag “Asia’s World City”. Hong Kong attracts variety of consumers from all around the world and the tourism industry needs the research the factors that are affecting customer satisfaction in Hong Kong luxury hotel industry. This study proposed a SEM to find out the relationship among perceived quality, service quality, tangibles, reliability, responsiveness, assurance, empathy that affecting customer satisfaction in Hong Kong luxury hotels. The research framework of this study consist of three constructs including perceived quality, service quality, and customer satisfaction. Seven hypotheses are proposed to study and four hypotheses are accepted. Three hypotheses are rejected and to have no significant relationship with customer satisfaction in this study. At last, the relationship among seven hypotheses effects on customer satisfaction are discussed and suggestions for unsupported hypotheses in context of enhancing customer satisfaction in Hong Kong luxury hotels are discussed as well.